Neonatal lung ultrasonography score after surfactant in preterm infants: A prospective observational study. Issue 1 (11th November 2019) - Perri, Alessandro; Tana, Milena; Riccardi, Riccardo; Iannotta, Rossella; Giordano, Lucia; Rubortone, Serena Antonia; Priolo, Francesca; Di Molfetta, Domenico V.; Zecca, Enrico; Vento, Giovanni
Abstract: Objective: To assess changes in neonatal lung ultrasonography score (nLUS) after surfactant administration in preterm infants with respiratory distress syndrome (RDS). Working Hypothesis: The reduction of nLUS score before (nLUSpre), 2 hours (nLUS2h), and 12 hours (nLUS12h) after surfactant administration to identify patients who will not need a second treatment. Study Design and Setting: Prospective observational study in the tertiary neonatal intensive care unit. Patients Selection: Forty‐six preterm neonates with RDS of 32 weeks median gestational age (IQR 30‐33) and mean birth weight of 1650 ± 715 g. Methodology: Lung ultrasonography was performed before, 2 hours, and 12 hours after surfactant administration in preterm infants with RDS needing surfactant treatment. Resulting nLUS was analyzed. Results: The Wilcoxon signed‐rank test demonstrated an nLUS lowering after 2 hours ( P < .001) and 12 hours ( P < .001) from surfactant administration. Sixteen newborns required surfactant retreatment with median gestational age of 32 weeks (IQR 29‐33) and mean birth weight of 1519 ± 506 g.The receiver operating characteristic analysis for the nLUS2h yielded an area under the curve of 0.80 (95% confidence interval, 0.76‐0.85; P < .001). A nLUS2h ≥7 showed a sensitivity of 94% and a specificity of 60% for needing a second treatment with surfactant. Conclusions: In preterm infants with RDS requiring surfactant treatment, nLUS evaluated 2 hours after surfactant administration can be used to identify patients who will not need a second treatment.